Simplified design method for geocell-stabilized unpaved roads on weak subgrade - Han, Jie; Pokharel, Sanat Kumar (Frontiers in Built Environment, 2025)
Geocells have been successfully used to stabilize granular bases for unpaved roads over weak subgrade subjected to traffic loading. Unfortunately, no well-accepted design method is available in the literature. This paper presents the development of a simplified design method for this application by modifying the simplified design method available for the geogrid-stabilized bases over weak subgrade. This design method was calibrated based on the test results from the large-scale cyclic plate loading tests and the moving wheel tests on geocell-stabilized granular bases over weak subgrade. The California Bearing Ratios of the subgrade and base course, the number loading cycles or wheel passes required for 50–75 mm permanent deformation, the height of geocell, and the thickness of the base course were the variables used for the calibration. The calibrated design method was used to verify the test results and yielded a good comparison. In addition, a design example is presented to illustrate how this method can be used in practice.